Reform of the 1961 Vienna Convention on Diplomatic Relations and Its Challenges - Ria Wulandari (Faculty of Law, Universitas Pekalongan, 2025)
The 1961 Vienna Convention on Diplomatic Relations is a key international treaty that outlines fundamental principles governing diplomatic relations between states. It provides privileges and immunities to diplomatic agents to ensure the effective performance of their functions and to maintain stable international relations. However, in practice, various challenges have emerged that highlight the need for reform of the convention’s provisions. Violations of diplomatic immunity—such as abuse of diplomatic status for personal, commercial, or even criminal purposes—have raised global concern. Reforming the Vienna Convention of 1961 is not an easy task due to political resistance among member states, fears of disrupting diplomatic stability, and the complexity of establishing new legal norms that gain universal acceptance. This paper employs a normative legal research method, focusing on international legal instruments, customary international law, and state practices to assess the feasibility and implications of reforming the convention. The findings aim to contribute to the discourse on updating international legal frameworks in the realm of diplomatic relations.